Hubungan Kepribadian Neuroticism dengan Pertimbangan Protokol Kesehatan dalam Konsumsi Produk selama Pandemi Covid-19 - Immanuel Yosua; Joan Devina Jonatan; Calista Khosasi; Marcellio Adrian Aridewo; Rafael Angkasa Pilartomo; Grace Avrat Valentina; Rayini Dahesihsari (Universitas Andalas, 2022)
This study aims to see the relationship between neuroticism and the consideration of health protocols in product consumption during the Covid-19 pandemic. Although various studies have shown a relationship between individual differences and adherence to health protocols during the pandemic, there have not been many studies that specifically discuss the relationship of neuroticism with health protocol considerations in product consumption during the Covid-19 pandemic. This study used a quantitative method with a survey design. A total of 1058 respondents with an age range of 18-25 years participated in this study, which was obtained using a convenience sampling technique. Correlation analysis using Spearman's Rank Order Correlation test showed that there was a positive relationship between Neuroticism personality type and health protocol considerations in product consumption (rs = .139, p<.001) although the correlation strength was weak. The results of this study show how a person considers a health protocol in product consumption is not solely determined by personality but also other contextual factors.